(untitled) (Società e diritti, 2019)
This work deals with the role of the social scientist in the production process of knowledge (method) that can be called scientific, considered in the light of the responsibility that the researcher takes in critical terms towards the reality being analyzed and self-criticism against the activity carried out, in order to avoid the risks associated with easy exploitations or suspected inactivity. Key words: sociology of law, role, social scientist, scientific knowledge, method, research, reflexivity, risks